EphA2-Dependent Molecular Targeting Therapy for Malignant Tumors - Biao-xue, RONG; Xi-guang, CAI; Shuan-ying, YANG; Wei, LI; Zong-juan, MING (Current Cancer Drug Targets, 2011)
Clarification of the molecular mechanisms of oncogenesis and drug resistance is a prerequisite for the development of new treatment strategies like molecularly targeted therapies. Recent studies demonstrate that EphA2 is overexpressed in human cancers and that EphA2 increases tumor invasion and survival. Thus, an EphA2 receptor antagonist, such as a specific tyrosine kinase inhibitor (in the form of an antibody, small molecule, peptide, or siRNA) or an antibody-drug conjugate that targets the EphA2 receptor could be the basis for a novel targeted antineoplastic therapy. This review summarizes the role of EphA2 in tumorigenesis and the development of EphA2 receptor antagonists as candidate anti-cancer agents. We suggests that continued research into the function of EphA2 signaling in the pathobiology of neoplasia could lead to more rationally designed therapeutics targeting EphA2 in solid tumors.
Keywords: microvessel density